(Frequency of CYP2C19 Gene Polymorphisms (SNP) and its Impact on Clinical Outcome in Ischemic Heart Disease Patients Taking Clopidogrel after percutaneous coronary intervention (PCI - Abdel- Sattar, Ahmed Shawky; Al Zawahiri, Mokhtar Mohammed Ibrahim; Thabet, Hussein Hassan; Baraka, Khaled Abdul- Ghani (Journal of medical and pharmaceutical sciences, 2019)
Clopidogrel an oral thienopyridine derivative capable of inhibiting platelet activation. Clopidogrel is prodrug that is converted into an active drug by hepatic cytochrome CYP2C19, CYP2C19*2 and CYP2C19*3 polymorphic alleles are considered to be important loss- of- function alleles resulting in diminished response to clopidogrel. our study aimed to detect frequency of CYP2C19 gene polymorohisms and its impact on clinical outcome in ischemic heart disease patients taking clopidogrel. Matrial and methods: blood samples were collected from 102 ischemic heart disease patients and the frequency alleles was determined by PCR and all patients were followed by clinical assessment and invasive and non- invasive cardiac investigations .Results:. frequency of CYP2C19*1 was 49%, CYP2C19*2 was 15% and CYP2C19*3 was 1%, CYP2C19*17 was 34%, patients with recurrent ischemic attacks 37patients (35.8%), from those patients, 10 patients were normal metabolizer (27%), and 27 patients were abnormal metabolizers(73%) with p- value 0.047 to myocardial infarction and 0.020 to unstable angina. Conclusion:. Asignificance relation was found between CYP2C19polymorphism and recurrent ischemic attacks in this study and multicenter studies are required to confirm this results.
Keywords: clopidogrel; thienopyridine; cytochrome; metabolizer